The Relationship between Parental Mediation and Facebook Victimization and in-Person Victimization, Both Directly and Indirectly Being Mediated by The Intensity of Facebook Use by Middle School Students in An International School in Bangkok, Thailand - Saunders, Claudia; Varma, Parvathy (Scholar: Human Sciences, 2016)
The primary purpose of this study was to investigate the relationship between parental mediation and victimization that occurs from being bullied on Facebook, and victimization from bulling in-person, both directly and indirectly being mediated by the intensity of Facebook use. Also examined in the study was the overall difference in frequencies from victimization on Facebook and victimization which occurs from bullying in-person, amongst middle school students at an International school in Bangkok, Thailand. All students who participated in the study were below the authorized age for Facebook use; 13. A total of 93 students participated in the study by filling out a self-administered survey questionnaire designed to measure the primary variables of the study (styles of parental mediation: intensity of Facebook use, victimization that occurs from bullying on Facebook, and victimization that occurs from in-person bullying). Results from the path analysis showed that certain forms of parental mediation directly influenced student’s responses per intensity of Facebook use, victimization on the Facebook platform, and victimization that occurs in person. Also examined in the final analysis were the differences from overall victimization experiences on Facebook and those that occur in-person. The study found that students with parents that use parental mediation - guidance as a strategy for media use showed less frequency for intensity of Facebook use, victimization via Facebook bullying, and victimization from bullying in-person. Results also revealed that more students, overall, reported higher incidents of victimization from bullying on Facebook, than victimization that occurs from bullying face-to-face. The study’s conclusions, implications, and avenues for future research are discussed.